Optimizing Mediation for Land Dispute Settlements: A Socio-Legal Analysis from Indonesia - Soediro, Soediro; Nur’aeni, Nur’aeni; Kartini, Ika Ariani; Dewi, Shintyana (Kosmik Hukum, 2024)
Land disputes are a prevalent legal issue in Indonesia, often arising from conflicting ownership claims among individuals, families, or communities. Mediation has emerged as an alternative dispute resolution mechanism that offers a more efficient, expeditious, and flexible approach compared to litigation. This study aims to examine the key factors influencing the effectiveness of mediation in resolving land disputes in Plaosan Village, Wonosari District, Malang Regency, as well as the challenges faced by the disputing parties. Employing a normative juridical research method with a descriptive-analytical approach, this study integrates both primary and secondary data collection techniques. The findings highlight that the success of mediation is significantly influenced by public awareness, the competence of mediators, and the legal framework supporting mediation practices. Strengthening regulatory mechanisms and enhancing public understanding of mediation are crucial in optimizing its role as a viable solution for land disputes in rural communities.